Antisocial Behaviors as Indicators of Latent School Dysfunction in Urban Morocco: a Phenomenology Study - Ouladhadda, Aziz; Azhar, Adil (International Journal of Language and Literary Studies, 2023)
This present research delves into the subjective experiences of EFL high school teachers in Morocco, elucidating their daily encounters with disruptive and anti-social behaviors and the coping mechanisms they employ. Conducted within the theoretical framework of structural functionalism, the study aims at measuring the extent to which schools as socialization institutions serve their designated social roles. A phenomenological methodology is employed, allowing five high school teachers to freely share and reflect on their lived experiences with regard to the topic under investigation. Semi-structured interviews were used to collect the data, which offered ample freedom for informants to voice their perceptions, feelings, sufferings, and to suggest practical solutions. From the testimonies of participants, three primary themes emerged. First, the Moroccan school is now embarking on undeclared roles pertaining to security and social order rather than to education. Second, the immense suffering experienced by teachers has a substantial negative impact on their professional performances, which, in turn, affects students’ academic achievements. Third, informants recognize disruptive behavior as a symptom of school dysfunction, and attribute it to teacher disempowerment, ineffective school legislations, the absence of a collaborative environment, the local authorities, the media and the family.